A clustering allocation and scheduling analysis approach for multiprocessor dependent real-time tasks. (31st March 2023) - Mrabet, Faten; Karamti, Walid; Mahfoudhi, Adel
The ultimate objective in this paper is to propose a new method for dependent tasks clustering by considering the inter-tasks communication cost, the inter-clusters communication cost (inter-calculation units), the precedence impact and the execution cost. The optimal Munkres assignment algorithm is used for an optimal total execution cost. Tasks deadlines and their imposed precedence obligations are taken into consideration to lead a fast and safe exact scheduling analysis of each partition separately while giving pertinent feedback. Experimental results highlight the effectiveness of the proposed approach by comparing it with optimal ones. The outcome shows better results in the total execution cost and gives exact scheduling analysis results.